Determining the low temperature Cr solubility limit and precipitation mechanisms in Fe-Cr alloys with proton irradiations and thermal aging - Yajie Zhao; Yao Li; Arunodaya Bhattacharya; Jonathan D. Poplawsky; Jean Henry; Steven J. Zinkle (Materials & Design)
FeCr based steels, widely deployed for various industrial applications, are prone to embrittlement from Cr-rich alpha prime (α’) precipitation. However, experimental α/α + α’ phase boundary assessments at low-to-intermediate temperatures are challenging due to slow Cr diffusivity below 450 °C, and existing CALPHAD predictions are inaccurate. To overcome these limitations, proton irradiations were used to enhance diffusion in Fe-(5–18)%Cr at 250–450 °C, and thermal aging was performed at 450–500 °C for up to one year. The resulting precipitate morphology and composition were examined using atom probe tomography, with supporting analysis from scanning-transmission-electron-microscopy (STEM). In Fe-18Cr, thermal aging resulted in α’ formation across all temperatures. Proton irradiation produced precipitate morphologies comparable to those observed after aging, indicating radiation-enhanced precipitation. In the less concentrated FeCr alloys, radiation-enhanced α’ formed in Fe-10Cr at 350 °C. At 250 °C, Fe-5Cr exhibited radiation-induced Cr precipitation (attributed to segregation of Cr to dislocation loops), whereas radiation-enhanced and −induced precipitation both occurred in Fe-(8–10)Cr. Despite mild ballistic mixing and radiation-induced segregation, a reasonable equilibrium phase boundary was established using a modified regular solution equation. This experimental Cr solvus line can guide alloy design to mitigate α’-related embrittlement, and benchmark thermodynamic calculations of FeCr system.